Design and implementation of a web-based administrative information system for PUSHANSIBER - Rizal Gian Febriantama; Bagus Hendra Saputra; Sembada Denrineksa Bimorogo; Nadiza Lediwara (Jurnal Mandiri IT, 2026)
The design and implementation of a web-based administrative information system for Subbagian Tata Usaha at Pusat Pertahanan Siber (Pushansiber), Ministry of Defense, Indonesia, addressed critical inefficiencies in manual Excel and paper-based processes causing data redundancy, workflow delays, and limited real-time access. Using Rapid Application Development (RAD) methodology, this research developed an integrated system with innovative features for high-security defense environments: five-tier Role-Based Access Control (RBAC), Server-Sent Events (SSE) for real-time notifications, automated leave quota validation, and competency mapping algorithms with gap analysis. This work contributes a validated framework for administrative digitalization in high-security defense environments by integrating five administrative workflows into a unified platform with RBAC, real-time SSE notifications, and comprehensive audit logging addressing the literature gap where existing studies overlooked security-sensitive requirements in government contexts. Black Box testing with 20 scenarios validated functionalities, demonstrating quantifiable improvements: leave approval time reduced 85% (3-5 days to 4 hours), personnel data retrieval improved from 15-20 minutes to 30 seconds, missed tasks decreased from 20% to below 5%, announcement delivery achieved 97%, and data entry errors reduced to below 2%. This research establishes a replicable model for defense administrative transformation, contributing empirical evidence to public sector digital transformation literature.